(untitled) (Research, Society and Development, 2018)
This experience report aims to analyze and reflect the application of a teaching strategy, in second year high school classes, of a school in Vale do Taquari, Rio Grande do Sul. The different strategies applied in the classroom challenge the student to countless actions: the defense of ideas, the power of argumentation, the judgment and the decision making. It should be noted that the records referring to the results were made from observations, notes and audio recordings during the development of activities. In view of these considerations and observing that the students presented difficulties regarding the argumentation and interpretation of situations, the Simulated Jury strategy was developed. According to the students’ reports, it was possible to perceive that they are accustomed to routine activities in the classroom and emphasize that the strategy was a rich form of exchange of dialogues, discussions and debate, supported in a real situation. Since group dynamics are attractive and engaging because of their motivational and constructive nature, they can be used as pedagogical proposals in any discipline. In addition, it was realized that they contributed to the development of interpretation and argumentation of the students involved, who started to put their ideas with clarity.